Prevalence, distribution, and inequitable co-occurrence of mental ill-health and substance use among gender and sexuality diverse young people in Australia: epidemiological findings from a population-based cohort study - Bailey, Sasha; Newton, Nicola; Perry, Yael; Davies, Cristyn; Lin, Ashleigh; Marino, Jennifer L; Skinner, S R; Garlick-Bock, Sophia; Nguyen, Ha; Mitrou, Francis; Barrett, Emma (My University, 2024)
To estimate the prevalence, distribution, and co-occurrence of mental ill-health and substance use among gender and sexuality diverse young people relative to their cisgender and heterosexual peers in Australia using population-level, nationally representative data. We utilised Wave 8 (2018) data from the Longitudinal Study of Australian Children (N = 3037, Mage = 18.4) collected via an assessment protocol comprising interviews, direct observations, and assessments (on average 60 min per survey occasion). Weighted prevalence ratios and logistic regression models adjusted for demographic confounders were used to estimate the prevalence and distribution of mental ill-health (psychological distress, past 12-month self-harm thoughts and behaviours, past 12-month suicidal ideation, planning, attempt/s) and substance use outcomes (past 12-month cigarette, alcohol, and marijuana use) across gender identity (trans vs. cisgender), sexuality (gay/lesbian, bisexual, queer [those identifying with an 'other' sexuality identity that is not 'gay', 'lesbian', 'bisexual', or 'heterosexual'] vs. heterosexual) and sexuality diversity status (sexuality diverse vs heterosexual) subgroups. Sex-stratified prevalence rates and accompanying adjusted logistic regression models were also used to assess mental ill-health and substance use disparities by sexuality diversity status. Adjusted multinominal logistic regression models were used to test disparities in co-occurring outcomes by sexuality identity) sexuality status sub-groups, and Fisher's Exact Test of Independence for co-occurring disparities by gender identity (due to small sample size). All analyses used Wave 8 sample weights and adjusted for postcode-level clustering. Among gender and sexuality diverse participants, 59 - 64% reported high or very high levels of psychological distress, 28 - 46% reported past 12-month self-harm ideation or attempts, and 26 - 46% reported past 12-month suicidal ideation, planning, or behaviour. We found significant disparities in high/very high levels of psychological distress, self-harm behaviours and suicidal behaviours among trans participants (adjusted odds ratios (aORs) ranged from 3.5 to 5.5) and sexuality diverse participants (aORs ranged from 3.5 to 3.9), compared with cisgender and heterosexual participants, respectively. Highest disparities in any past 12-month self-harm and suicidal behaviours appeared most pronounced among trans participants and queer participants compared with their cisgender, heterosexual counterparts. Minor differences by sex among sexuality diverse participants were observed for select mental ill-health outcomes. Sexuality diverse participants, and particularly sexuality diverse females, were significantly more likely to report past 12-month cigarette use and past 12-month marijuana use (adjusted odds ratio (aORs) ranging 1.4-1.6). Trans young people were at significantly elevated risk of mental ill-health in co-occurrence with cigarette and marijuana use compared with their cisgender peers (Fisher's Exact Test of Independence p < 0.05 for all), whereas sexuality diverse young people were at greater risk of co-occurring mental ill-health and cigarette co-use and marijuana co-use, compared with their non-sexuality diverse peers (adjusted multinomial odds ratios (aMORs) ranging 2.2-6.0). Mental ill-health, substance use, and their co-occurrence disproportionately affects gender and sexuality diverse young people in Australia. Further research should study the longitudinal development of these disparities through adolescence, with close attention to the social, embodied contexts of substance use among LGBTQ + young people with the view to building LGBTQ + affirming models of harm reduction.
Social Psychiatry and Psychiatric Epidemiology
Keywords: Adolescents; Comorbidity; Gender; Mental health; Sexuality; Substance use; Adolescents and youth; Childhood and child development; Gender; Health and wellbeing; Lifestyle